2019
DOI: 10.1002/aur.2229
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐wide association analysis of autism identified multiple loci that have been reported as strong signals for neuropsychiatric disorders

Abstract: Autism is a common neurodevelopmental disorder with a moderate to a high degree of heritability, but only a few common genetic variants that explain the heritability have been associated. We performed a genome‐wide transmission disequilibrium test analysis of a newly genotyped autism case–parent triad samples (127 trios) in Han Chinese, identified top association signals at multiple single nucleotide polymorphisms (SNPs), including rs9839376 (OR = 2.59, P = 1.27 × 10−05) at KCNMB2, rs6044680 (OR = 0.319, P = 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 83 publications
0
14
0
Order By: Relevance
“…Although further studies will be needed to disentangle the biological meaning of these findings, we could speculate that the observed pathway-level negative genetic correlation between ASD and MetS/T2DM might reflect higher complexity of reciprocal regulation between monoamine and insulin signalling at the CNS and peripheral level (12). Interestingly, while the insulin processing pathway is generally involved in the generation and subsequent exocytosis of insulin-containing granules, individual genes within this set (i.e., syntaxin-1A (STX1A), vesicle-associated membrane protein 2/synaptobrevin-2 (VAMP2), proprotein convertase subtilisin/kexin type 2 (PCSK2)) have also been linked to presynaptic neurotransmission and previously been associated with autism, intellectual and neurodevelopmental disabilities (27, 28).…”
Section: Discussionmentioning
confidence: 99%
“…Although further studies will be needed to disentangle the biological meaning of these findings, we could speculate that the observed pathway-level negative genetic correlation between ASD and MetS/T2DM might reflect higher complexity of reciprocal regulation between monoamine and insulin signalling at the CNS and peripheral level (12). Interestingly, while the insulin processing pathway is generally involved in the generation and subsequent exocytosis of insulin-containing granules, individual genes within this set (i.e., syntaxin-1A (STX1A), vesicle-associated membrane protein 2/synaptobrevin-2 (VAMP2), proprotein convertase subtilisin/kexin type 2 (PCSK2)) have also been linked to presynaptic neurotransmission and previously been associated with autism, intellectual and neurodevelopmental disabilities (27, 28).…”
Section: Discussionmentioning
confidence: 99%
“…High comorbidity rates of ADHD were observed across ASD [32]. An increasing amount of evidence suggests that ASD and ADHD may have shared genetic risk patterns [33][34][35][36]. Family-based studies show that siblings of patients with ADHD have an increased risk of developing ASD symptoms [34], while studies of twins show that common genetic factors may explain 50% to 70% of the covariance between ASD and ADHD symptoms [35,37].…”
Section: Central Symptoms In Asdmentioning
confidence: 99%
“…Thus, both accessory subunits are able to reduce the BK channel activity through different mechanisms, leading to multiple possibilities for alteration of neuronal excitability. While only β4 function is implicated in ASD-related learning disability at present, genome-wide association studies have recently identified KCNMB2 SNP associations in autism case trios and other neuropathological states ( Beecham et al, 2014 ; Kimbrel et al, 2018 ; Xia et al, 2020 ). β2 expression has been detected in several areas of the brain implicated in ASD ( Brenner et al, 2000b ; Nordahl et al, 2012 ; Schumann et al, 2004 ; Stoodley, 2014 ).…”
Section: Introductionmentioning
confidence: 99%